Antithrombotic Therapy in a Prospective Trial of a Pediatric Ventricular Assist Device - Steiner, Marie E. (ASAIO J, 2016)
Efficacious ventricular assist device (VAD) support in pediatric patients depends on successful antithrombotic management. The experience with antithrombotic management for the EXCOR Pediatric VAD Investigational Device Exemption (IDE) study is described. All 68 children in North America enrolled in the IDE study from May 9, 2007 to December 10, 2010 are included. The Edmonton Anticoagulation and Platelet Inhibition Protocol was provided for management guidance. Monitoring parameters, drug dosing, targeted serious adverse events, and pump changes were reviewed. Major bleeding occurred in 43% of all subjects with most events occurring within 14 days of implantation. Bleeding events were probably/definitely related in 24% to antithrombotic management. Neurologic events occurred in 28% of subjects and were probably/definitely related in 9% to antithrombotic therapy intensity. Most neurologic events occurred between 4 and 30 days postimplantation and sporadically thereafter. Pump change occurred in 56% of subjects. Use of an antithrombotic protocol for enrolled subjects was possible in this multicenter study. Incidence of significant bleeding and thromboembolic events was acceptable when balanced against life-saving benefits of VADs. Further studies are needed to optimize the antithrombotic management of this patient population.